KURIKULUM PENDIDIKAN VOKASI PADA ERA REVOLUSI INDUSTRI 4.0 - Unung Vera Wardina; Nizwardi Jalinus; Lise Asnur (LPPM Universitas Terbuka, 2019)
Vocational education purpose is to produce ready-to-work graduates who have the relevant skills for current job employment. Entering the industrial revolution era 4.0 there were massive changes in various industries and workers' ability needs. This article intends to examine the implications of the industrial revolution 4.0 era for vocational education curriculum. Based on the study of various sources and business practices, it is necessary to develop vocational education curriculum that are in accordance with the era of industrial revolution 4.0 and relevant to answering the needs of new skills, such as the ability to create and manage coding, big data, and artificial intelligence. The vocational curriculum needs to apply blended learning, which integrates face-to-face and online learning, so as to more effectively build graduates' abilities and skills. The curriculum also needs to contain mastery of 4.0 competencies such as data literacy, technology literacy and human literacy. In order for the vocational education curriculum to have a broad impact, the government, educational institutions, industries must work together to revitalize the approach and content of the vocational education curriculum. Teachers must also be able to implement good learning to produce optimal graduate performance. Pendidikan vokasi merupakan pendidikan yang menghasilkan lulusan siap kerja yang memiliki keterampilan sesuai kebutuhan dunia kerja. Memasuki era revolusi indusri 4.0 terjadi perubahan yang masif pada perbagai industri dan kebutuhan kemampuan pekerja. Artikel ini bermaksud mengkaji implikasi era revolusi industri 4.0 bagi kurikulum pendidikan vokasi. Berdasarkan kajian berbagai sumber dan praktek bisnis, diperlukan pengembangan kurikulum pendidikan vokasi yang sesuai dengan era revolusi industri 4.0 dan relevan menjawab kebutuhan keterampilan baru, seperti kemampuan membuat dan mengelola coding, big data, dan artificial intelligence. Kurikulum vokasi perlu menerapkan pembelajaran blended learning, yang mengintegrasikan pembelajaran tatap muka dan online, supaya lebih efektif membangun kemampuan dan ketrampilan lulusan. Kurikulum juga perlu memuat penguasaan kompetensi 4.0 seperti literasi data, literasi teknologi dan literasi manusia. Agar kurikulum pendidikan vokasi menghasilkan dampak yang luas, pemerintah, lembaga pendidikan, industri harus bersinergi untuk merevitalisasi pendekatan dan isi kurikulum pendidikan vokasi. Pengajar juga harus dapat menyelenggarakan pembelajaran yang baik untuk menghasilkan kinerja optimal lulusan.